Gliding Motility and Expression of Motility-Related Genes in Spreading and Non-spreading Colonies of Flavobacterium columnare - Penttinen, Reetta; Hoikkala, Ville; Sundberg, Lotta-Riina (Frontiers in Microbiology, 2018)
Gliding motility facilitates the movement of bacteria along surfaces in many Bacteroidetes species and results in spreading colonies. The adhesins required for the gliding are secreted through a gliding motility-associated protein secretion system, known as the type IX secretion system (T9SS). The fish pathogen Flavobacterium columnare produces spreading (rhizoid [Rz], soft [S]) and nonspreading (rough [R]) colony types, of which only the spreading Rz type is virulent. In this study, we explored the spreading behavior of these colony types by microscopic imaging and measured the expression of genes associated with gliding motility and T9SS (gldG, gldH, gldL, sprA, sprB, sprE, sprF, sprT, and porV) under high and low resource levels by using RT-qPCR (Reverse Transcription quantitative PCR). The spreading colony types responded to the low resource level with increased colony size. The nonspreading colony type, as well as the cells growing under high nutrient level expressed only moderate cell movements. Yet, a low nutrient level provoked more active gliding motility in individual cells and increased spreading by cooperative gliding. The gene expression survey demonstrated an increased expression level of sprA (a core component of T9SS) and sprF (needed for adhesin secretion) under low nutrient conditions. Surprisingly, the expression of gliding motility genes was not consistently associated with more active spreading behavior. Furthermore, no genetic differences were found between spreading and nonspreading colony types in the studied genes associated with gliding motility. Our study demonstrates that environmental nutrient level is an important regulator of both gliding motility and the expression of some of the associated genes. These results may help to understand the connections between nutrient concentration, gliding motility, and virulence of F. columnare.